Breaking through the noise : presidential leadership, public opinion, and the news media - Eshbaugh-Soha, Matthew, 1972- (Stanford University Press, 2011)
"Modern presidents engage in public leadership through national television addresses, routine speechmaking, and by speaking to local audiences. With these strategies, presidents tend to influence the media's agenda. In fact, presidential leadership of the news media provides an important avenue for indirect presidential leadership of the public, the president's ultimate target audience. Although frequently left out of sophisticated treatments of the public presidency, the media are directly incorporated into this book's theoretical approach and analysis. The authors find that when the public expresses real concern about an issue, such as high unemployment, the president tends to be responsive. But when the president gives attention to an issue in which the public does not have a preexisting interest, he can expect, through the news media, to directly influence public opinion. Eshbaugh-Soha and Peake offer key insights on when presidents are likely to have their greatest leadership successes and demonstrate that presidents can indeed "break through the noise" of news coverage to lead the public agenda"--Publisher.
Keywords: Presidents -- United States.; Communication in politics -- United States.; Government and the press -- United States.; Political leadership -- United States.; Presidents -- Press coverage -- United States.; Press and politics -- United States.; Public opinion -- United States.; Public relations and politics -- United States.; Présidents -- États-Unis.; Communication politique -- États-Unis.; État et presse -- États-Unis.; Leadership politique -- États-Unis.; Présidents -- Conférences de presse.; Opinion publique -- États-Unis.; Relations publiques et politique -- États-Unis.; POLITICAL SCIENCE -- Political Process -- Leadership.; Communication in politics; Government and the press; Political leadership; Presidents; Presidents -- Press coverage; Press and politics; Public opinion; Public relations and politics; United States